‘Joined-Up’ Government: An integrated response to communal violence in Northern Ireland? - Knox, Colin (Policy and Politics, 2003)
The growing recognition that social problems are multi-faceted and need to be tackled in a way which cut-across traditional departmental boundaries has heralded the advent of joined-up government. Yet this new emphasis does not appear to have permeated the provision of public services in Northern Ireland in their response to the increasingly pervasive social problem of communal violence perpetrated by paramilitaries against those suspected of committing crime within their own communities. This paper examines the response of governmental and non-governmental agencies to this issue and questions whether victims of violence could benefit from an integrated approach. A deep suspicion and mistrust of the statutory authorities and the ‘undeserving’ character of victims currently militate against a joined-up approach.
Keywords: Joined-up; Violence; Northern Ireland; Criminal justice